El Excentrico, 1977-04-05 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
April 5, 1977 [5 de abril de 1977]. Ano 28, No 1. Cover contains a portrait of singer Linda Vera, who would be performing the the El Rey Arturo around the time of this issue's release. The headline reads, "Linda Vera: Mexico's Sensational Cantante Currently Appearing at El Rey Arturo."